A multilevel analysis of implicit and explicit CSR in French and UK professional sport. Issue 1 (1st January 2019) - François, Aurélien; Bayle, Emmanuel; Gond, Jean-Pascal
ABSTRACT: Research question: This paper examines the ways in which French and UK professional sports clubs implement and communicate their CSR policies. In addition to identifying similarities and differences between CSR practices in the two countries, our analysis extends and adapts the implicit-explicit CSR framework to the field of sport. Research methods: We used a mixed methods approach to analyse qualitative and quantitative data on the CSR strategies of 66 professional rugby union (Top 14, Aviva Premiership Rugby) and football (Ligue 1, Premier League) clubs that participated in the 2017–2018 season. Results and findings: We found major differences in CSR communication between France and the UK. Communication by French clubs tends to highlight sport's values, involve few media channels, whereas communication by UK clubs explicitly vaunts their social responsibility and involves numerous channels. In the case of CSR implementation, there are similarities between French and UK clubs, especially in the fields their CSR initiatives cover (e.g. health, diversity), as well as differences. However, the scope of initiatives varies more between sports than between countries, with football demonstrating a more international outlook than rugby. Implications: This article expands Matten and Moon's [(2008). 'Implicit' and 'explicit' CSR: A conceptual framework for a comparative understanding of corporate social responsibility. Academy of Management Review, 33 (2), 404–424] implicit-explicit CSR framework by identifying the influence of interactions between sectorial/field-level factors and national/macro-level factors on CSR practices, and by distinguishing between CSR communication and CSR implementation. Our results throw light on the shift from implicit to explicit CSR in French professional sport.